Pain experience, expression and coping in boys and young men with Duchenne Muscular Dystrophy – A pilot study using mixed methods. (July 2016) - Hunt, Anne; Carter, Bernie; Abbott, Janice; Parker, Arija; Spinty, Stefan; deGoede, Christian
Abstract: There is limited research exploring the pain experience of boys and young men with Duchenne Muscular Dystrophy. Methods: We conducted a mixed-methods pilot study to assess the feasibility of using particular measures of pain, pain coping and quality of life within semi-structured interviews with boys and young men with Duchenne Muscular Dystrophy and a postal survey of their parents. Non-probability, convenience sampling was used. Results: Twelve young men aged 11–21 years (median 15 years), three of whom were still ambulant, and their parents/guardians were recruited. The measures used were acceptable to the young men and demonstrated potential to provide useful data. Two-thirds of young men suffered from significant daily pain which was associated with reduced quality of life. Pain complaints were largely kept within the family. Young men's pain-coping strategies were limited by their restricted physical abilities. Statistical power based on these preliminary results suggests a study of approximately 50 boys/young men which appears feasible. Conclusions: Further study is needed to explore acceptable and effective methods of pain management in this population and ways of enhancing pain-coping strategies. In clinical practice, assessment of pains and discomfort should form part of all routine consultations. Highlights: We add evidence of significant pain in young men with Duchenne Muscular Dystrophy. We provide insights into their pain experience, pain coping and quality of life. Young men with moderate or worse pain daily had poorer quality of life. They do not readily report pain outside of the family. Clinicians need to ask them. We provide preliminary data to inform power and size for a future study.